Knowledge, Attitude, and Practice (KAP) Study on Dengue Fever among Medical Students in Dera Ismail Khan, Pakistan: Knowledge, Attitude, and Practice Study on Dengue Fever Among Medical Students - Ali, Nawazish; Iqbal, Anil; Rehman, Fazal Ur; Osama, Mohammad; Khalid, Muhammad; Jamal, Muazzam (Pakistan Journal of Health Sciences, 2024)
Dengue is a public health problem and a leading mosquito-borne viral disease. In Pakistan, the dengue virus has been the source of several epidemics. Objective: To find frequency, distribution, and association of KAP regarding dengue fever among students with gender and type of Students. Methods: This descriptive cross-sectional study using stratified random sampling was conducted in the Gomal Medical College (GMC). Sample size 235, an equal proportion of students from each class were randomly selected. Data were analyzed by using SPSS version 23.0. For inferential statistics, 95% CI was used. The chi-square test was used with p < 0.05 considered significant. Results: Among 235 students, 111 (47.3%), and 214 (91.1%) had good knowledge and attitude respectively. Preventive practices were as follows: 127 (54%) had good practices, 65% used mosquito repellents, and 58% used mosquito nets. There was no association of KAP with gender. Among 87 pre-clinical students, 29 (33%), 77 (89%), and 44 (51%) had good Knowledge, Attitude, And Practice (KAP) respectively. Among 148 clinical students, 82 (55%), 137 (93%), and 83 (56%) had good KAP respectively. There was an association between knowledge and Type of students at p = .002. Conclusions: It was concluded that 47%, 91%, and 54% of students had good KAP respectively. KAP wasn’t associated with gender. The type of students was associated with knowledge while attitude and practice were not significant.